Асимптотичний аналіз крайових задач у тонких перфорованих областях з швидко змінною товщиною - Мельник, Т.А.; Попов, А.В. (Нелінійні коливання, 2010)
Для симметрического равномерно эллиптического оператора второго порядка с быстро осциллирующими коэффициентами изучено асимптотическое поведение решений смешанной неоднородной краевой задачи и спектральной задачи Неймана в тонкой перфорированной области с быстро переменной толщиной, а также установлены асимптотические оценки для разности между решениями начальных задач и соответствующих усредненных задач. Эти результаты были анонсированы в „Доповiдях АН України”, 1991, № 10. Новые результаты данной работы связаны с построением асимптотического разложения для решения смешанной однородной краевой задачи при дополнительных предположениях симметрии на коэффициенты оператора и тонкую перфорированную область. A mixed nonuniform boundary-value problem and a spectral Neumann problem are considered for the
second-order symmetric elliptic differential operator with quickly oscillating coefficients in a thin perforated
domain with rapidly varying thickness. The leading terms of asymptotics are constructed and asymptotic
estimates are proved for solutions of these problems. These results were announced in the Reports of the
Academy of Sciences of Ukraine, № 10 (1991). New results of this paper are connected with the construction of the asymptotic expansion for the solution to a mixed uniform boundary-value problem under additional assumptions of symmetry for the coefficients of the operator and for the thin perforated domain.